The Multimedia Library as a General Perspective of the Library System - Amlinski, Lev (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
Globalisation of the information transmitting system in its complexity of scientific, educational, social and economic demands of society has lead to the formation of the international information market. Libraries have always held an important position in the entire information market and will continue to do so in the future.